Digital Literacy: Perceptions of Primary School Teacher Education Students - Nopitasari; Banu Setyo Adi; Sugeng Riyanto; Rahayu Condro Murti (Jurnal Ilmiah Sekolah Dasar, 2023)
This research is motivated by the emergence of the Covid-19 pandemic, which resulted in a change in the education system from conventional to online. This condition requires students to adapt to changes in the learning system. This study aims to analyze the perceptions of PGSD students regarding digital literacy in the era of the Covid-19 pandemic. This type of research is quantitative. This research uses a quantitative descriptive approach with a survey method. The population in this study were all 2018 class students, with a sample of 76 students. The data collection method uses a questionnaire with the help of Google Forms. The instrument used to collect data is a questionnaire. The data analysis technique uses descriptive analysis with the help of SPSS and Microsoft Excel. The results of the study show that, in general, the level of perception of PGSD students regarding digital literacy in the era of the Covid-19 pandemic is in the "Medium" category. It implies that the campus must pay more attention to the needs of its students. What can be done is to help increase digital literacy, especially by utilizing online platforms and operating learning applications.